Investigation of NOD1/CARD4 variation in inflammatory bowel disease using a haplotype-tagging strategy - Van Limbergen, J; Nimmo, E; Russell, R; Drummond, H; Smith, L; Anderson, N; Davies, G; Arnott, I; Wilson, D; Satsangi, J (Oxford University Press, 2007)
Both NOD1/CARD4 and NOD2/CARD15 are intracellular pattern-recognition receptors involved in the innate immune response. Germline NOD2/CARD15 variation has a definite effect on susceptibility to Crohn's disease (CD) and phenotype, although this contribution is weak in Scotland and Scandinavia. The NOD1/CARD4 gene lies within the putative inflammatory bowel disease (IBD) locus at 7p14.3. We have assessed, in detail, the influence of germline NOD1/CARD4 variation on IBD susceptibility and phenotype in the Scottish population. Two thousand two hundred and ninety-six subjects, including 356 children with IBD, were involved in parallel case–control and family-based association studies. Nine tagging single-nucleotide polymorphisms (SNPs) were selected based on HapMap data spanning the whole of the NOD1/CARD4 gene. Our case–control SNP analysis was powered to detect an effect size with OR 1.5 for IBD and OR 1.6 for CD. No significant associations were observed between any of nine the NOD1/CARD4 SNPs studied and IBD, CD or ulcerative colitis (UC) (P > 0.05 for all). Haplotype case–control analysis was also negative (P > 0.05 in IBD, CD and UC). Multimarker transmission disequilibrium testing analysis was negative (P > 0.05 in IBD, CD and UC). NOD2/CARD15 variant carriage had no influence on NOD1/CARD4 effect on IBD susceptibility. This study represents the first application of a gene -wide haplotype-tagging approach to assess, in detail, the contribution of NOD1/CARD4 in IBD.